2007
DOI: 10.1111/j.1524-4725.2007.34004.x
|View full text |Cite
|
Sign up to set email alerts
|

Is Levofloxacin Necessary to Prevent Postoperative Infections of Auricular Second-Intention Wounds?

Abstract: Levofloxacin is not necessary to prevent postoperative infections of auricular second-intention wounds after Mohs surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 15 publications
0
13
0
2
Order By: Relevance
“…The most commonly used antibiotics were cephalexin (SSI), clindamycin (if penicillin allergic), doxycycline (for methicillin‐resistant Staphylococcus aureus [MRSA]), amoxicillin (oral mucosa breach), and ciprofloxacin (ear). For the ear, cephalexin is recommended because risk of pseudomonas in cultures is low …”
Section: Resultsmentioning
confidence: 99%
“…The most commonly used antibiotics were cephalexin (SSI), clindamycin (if penicillin allergic), doxycycline (for methicillin‐resistant Staphylococcus aureus [MRSA]), amoxicillin (oral mucosa breach), and ciprofloxacin (ear). For the ear, cephalexin is recommended because risk of pseudomonas in cultures is low …”
Section: Resultsmentioning
confidence: 99%
“…The fourth‐generation quinolones include moxifloxacin and possess a wider spectrum, which includes Gram‐negative rods, Gram‐positive cocci, anaerobes, and atypical bacteria. Although these kill Streptococcus and MSSA, they have minimal antipseudomonal activity …”
Section: Pathogens By Body Sitementioning
confidence: 99%
“…Although Futoryan and Grande found only a 2.29% infection rate after Mohs procedures and excisions in general, the infection rate was much higher after Mohs surgery on the ear 19 . Nevertheless, in a recent study published by Mailler‐Savage and colleagues, there was no statistical significance between patients who receive a quinolone after Mohs surgery on the ear and those who received simple local wound care 20 . Historically, an antibiotic to cover gram‐negative organisms has been prescribed to patients before surgery on the ear because the ear was thought to be colonized with numerous organisms, including pseudomonas species 21 .…”
Section: Prophylaxis For Wound Infectionsmentioning
confidence: 97%
“…19 Nevertheless, in a recent study published by Mailler-Savage and colleagues, there was no statistical significance between patients who receive a quinolone after Mohs surgery on the ear and those who received simple local wound care. 20 Historically, an antibiotic to cover gram-negative organisms has been prescribed to patients before surgery on the ear because the ear was thought to be colonized with numerous organisms, including pseudomonas species. 21 Although pseudomonas may be cultured from the ear, recent studies have found that more than 95% of cultures from the external auditory canal and cerumen were gram-positive organisms with staphylococcus being the most commonly cultured species.…”
Section: Prophylaxis For Wound Infectionsmentioning
confidence: 99%